2022
DOI: 10.1101/2022.07.25.501387
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parallel duplication and loss of aquaporin-coding genes during the ‘out of the sea’ transition as potential key drivers of animal terrestrialization

Abstract: One of the most important physiological challenges animals had to overcome during terrestrialization (i.e., the transition from sea to land) is water loss, which alters their osmotic and hydric homeostasis. Aquaporins are a superfamily of membrane water transporters heavily involved in osmoregulatory processes. Their diversity and evolutionary dynamics in most animal lineages remain unknown, hampering our understanding of their role in marine-terrestrial transitions. Here, we interrogated aquaporin gene repert… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 141 publications
(295 reference statements)
1
0
0
Order By: Relevance
“…In this sense, among these orthogroups expanded in parallel we detected aquaporins (orthogroup OG0000253; Supplementary Table 2), a superfamily of membrane water and solute transporters such as glycerol or urea strongly involved in osmoregulation 26 . Moreover, this family was recently shown in a targeted analysis to have undergone parallel expansions across several non-marine animal phyla 27 , confirming the robustness of our methodological approach to detect such events. Moreover, a previous study based on a limited phylogenetic sampling suggested that a family of Zinc metalloproteinases with a potential role in reducing oxidative damage had expanded in the Stylommatophora gastropods ( 7).…”
Section: Parallel Genomic Expansions During Transitions Out Of the Ma...supporting
confidence: 75%
“…In this sense, among these orthogroups expanded in parallel we detected aquaporins (orthogroup OG0000253; Supplementary Table 2), a superfamily of membrane water and solute transporters such as glycerol or urea strongly involved in osmoregulation 26 . Moreover, this family was recently shown in a targeted analysis to have undergone parallel expansions across several non-marine animal phyla 27 , confirming the robustness of our methodological approach to detect such events. Moreover, a previous study based on a limited phylogenetic sampling suggested that a family of Zinc metalloproteinases with a potential role in reducing oxidative damage had expanded in the Stylommatophora gastropods ( 7).…”
Section: Parallel Genomic Expansions During Transitions Out Of the Ma...supporting
confidence: 75%